A review on the selection of lean production tools and techniques - Yahya, Mohd Shahir; Mohammad, Musli; Omar, Badrul; Ramly, Edly Ferdin (Asian Research Publishing Network (ARPN), 2016)
There has been numerous published literature related to lean production. However, very limited studies have been found focussing on the selection of lean production tools and techniques especially for Malaysian context. The review is based on the contemporary literature that published between year 2004 to 2014. The main databases used were Science Direct, Scopus and Emerald. The review gives general pictures of the selection and implementation of lean tools and techniques in various industries and the factors that affect the selection process. The analysis showed that there was no study yet on the selection of lean production tools and techniques specifically in Malaysia by using rational decision making process. Therefore, this gap requires further research on the selection of appropriate lean production tools and techniques by considering several critical decision criteria.